En underlig historia. Hjalmar Bergman och funktionalismen - Storskog, Camilla (Folia Scandinavica Posnaniensia, 2025)
In 1929, Hjalmar Bergman was commissioned to write a play for the opening ceremony of the 1930 Stockholm Exhibition, an event that established functionalism as the dominant trend in Swedish architecture. The rejection of his proposal by the progressive organisers, art historian Gregor Paulsson and architect Gunnar Asplund, was something of “an odd story” according to Bergman himself, who, in an interview, asserted that the play was refused “for functionalist reasons”, and because of the tribute it paid to traditional Swedish handicraft. Some time before the interview, Bergman had ironised about this contemporary expression of Modernism in his radio play Tankar om funktionalism (Thoughts about Functionalism). In this article, Bergman’s personal assessment of the functionalist doctrine, according to which the purpose of architecture should dictate its form, is discussed and related to the improbable room at the centre of the Borck family home in the novel Farmor och Vår Herre (1921; Thy Rod and Thy Staff, 1937). While earlier readings of the puzzling ‘rooms of wonder’ that appear in Bergman’s generally solid houses of fiction have applied psychological and biographical lenses to interpret what may look like purposeless nooks and crannies, this essay departs from the historical context to show Bergman’s understanding – if not appreciation – of functionalism.